Cryptocurrency Abuse for the Purposes of Money Laundering and Terrorism Financing: Policies and Practical Aspects in the European Union and North Macedonia - Ilijevski, Ice; Ilik, Goran; Babanoski, Kire (European Scientific Journal, ESJ, 2023)
The number of countries that express concern for the danger of using cryptocurrencies for illegal activities among which are money laundering and terrorism financing is increasing. Cryptocurrencies are virtual assets created and managed through advanced computer encryption and operate on a decentralized network known as a blockchain. The key issue of concern and attention in the world is the anonymity and pseudonymity of cryptocurrencies, which prevents proper monitoring of transactions by state institutions and allows the completion of suspicious transactions outside the regulated systems. The paper provides an overview and presentation of the existing European legal framework and the measures and activities undertaken by the Republic of North Macedonia, harmonized with the European ones, in the fight against money laundering and terrorist financing in the crypto sector.